Analisis Historis terhadap Teologi Gerakan Pentakostalisme - Daniel Sutoyo (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2018)
Abstract. The purpose of this paper is to explain the historical developments, doctrines and behaviors that appear in every Pentecostal movement, so that we can distinguish between the First Wave movement, the Classical Pentecost, the Second Wave Movement, the Charismatic Movement, the Third Wave Movement, the Sign Movement and the Miracles, and Fourth Wave Movement, New Apostolic Reformation Movement (NAR). The method in this study is the study of historical analysis on the history of the development of each wave movement Pentecostalism. Through the analysis it is concluded that every wave of the Pentecostal movement is a movement that comes from God, through the work of His Holy Spirit. Although in practice there is a distorted phenomenon, but can not be generalized and then assume everything is heretical.Abstrak. Tujuan penulisan ini adalah menjelaskan sejarah perkembangan, doktrin dan perilaku yang muncul setiap gerakan Pentakostalisme, sehingga kita dapat membedakan antara gerakan Gelombang Pertama, Pentakosta Klasik, Gerkan Gelombang Kedua, Gerakan Kharismatik, Gerakan Gelombang Ketiga, Gerakan Tanda-tanda dan Mujizat-mujizat, dan Gerakan Gelombang Keempat, Gerakan New Apostolic Reformation (NAR). Metode dalam penelitian ini adalah penelitian analisis historis terhadap sejarah perkembangan setiap gerakan gelombang Pentakostalisme. Melalui analisis tersebut disimpulkan bahwa setiap gelombang gerakan Pentakostalisme adalah sebuah gerakan yang berasal dari Tuhan, melalui karya Roh Kudus-Nya. Meskipun dalam praktiknya ditemukan fenomena yang menyimpang, namun tidak dapat digeneralisasikan dan kemudian menganggap semuanya sesat.